The Predictive Value of SII Combined with UHR for Contrast-Induced Acute Kidney Injury in Patients with Acute Myocardial Infarction After Percutaneous Coronary Intervention - Wang L; Xu Y; Zhang X; Ding J; Jin J; Zong J; Li F; Qian W; Li W (Dove Medical Press, 2024)
Linsheng Wang,1,* Yang Xu,2,* Xudong Zhang,1 Jiahui Ding,1 Jingkun Jin,1 Jing Zong,1 Fangfang Li,1 Weidong Qian,3 Wenhua Li1,4 1Institute of Cardiovascular Diseases, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 2Department of Cardiology, Xuzhou Central Hospital, Xuzhou, Jiangsu, People's Republic of China; 3Department of Cardiology, Wujin Affiliated Hospital of Nanjing University of Chinese Medicine, Changzhou, Jiangsu, People's Republic of China; 4Department of Cardiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Weidong Qian, Department of Cardiology, Wujin Affiliated Hospital of Nanjing University of Chinese Medicine, Changzhou, Jiangsu, People's Republic of China, Email qwd213161@163.com Wenhua Li, Department of Cardiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China, Email xzwenhua0202@163.comBackground: Contrast-induced acute kidney injury (CI-AKI) refers to the acute renal dysfunction caused by the injection of contrast agents. CI-AKI is currently a common complication after percutaneous coronary intervention (PCI).Objective: To investigate the predictive value of the combined systemic inflammatory index (SII) and urate/high-density lipoprotein cholesterol ratio (UHR) for CI-AKI after PCI in patients with AMI.Methods: A total of 1222 patients with AMI who underwent PCI were randomly divided into a training group and a validation group in an 8:2 ratio. According to the definition of CI-AKI diagnostic criteria, the training group was divided into CI-AKI group and non-CI-AKI group. Collect patient's blood and biochemical data, then calculate SII and UHR. The risk factors for CI-AKI were identified using LASSO and multivariate logistic regression analyses. A predictive column was created by using R language.Evaluate the predictive value of SII, UHR and their combination for CI-AKI after PCI using the area under the ROC curve (AUC).Results: Diabetes, Cystatin C, Diuretics, UHR, and LnSII were independent risk factors for CI-AKI in AMI patients after PCI. The ROC curve showed that the AUC of UHR and SII combined for predicting CI-AKI in AMI patients after PCI was 0.761 (95% CI: 0.709- 0.812), with a sensitivity of 65.20% and a specificity of 76.70%, which was better than the prediction by either factor alone.Conclusion: High SII and high UHR are risk factors for AMI, and their combination can improve the accuracy of predicting CI-AKI in AMI patients after PCI.The prognosis of CI-AKI in AMI patients is worse than in the general population.Keywords: serum uric acid, high-density lipoprotein cholesterol, neutrophils, lymphocytes, systemic immune-inflammatory index, contrast-induced acute kidney injury